A Interactive Learning Video Innovation Based on Problem-Based Learning to Improve Students' Metacognition in Grade IV of Elementary School - Made Haya Putri Darmawan; I Komang Sudarma (Jurnal Media dan Teknologi Pendidikan, 2025)
The low level of metacognitive ability among fourth-grade students in IPAS (Science and Social Studies) learning has emerged as a major issue affecting the quality of learning outcomes. The lack of variation in innovative learning media also hinders the development of students' higher-order thinking skills. This study aims to analyze, evaluate, and develop an interactive learning video based on Problem-Based Learning (PBL) using the ADDIE model to enhance students' metacognitive abilities. This research employs a development research approach with a one-group pretest-posttest design. The research subjects consist of 22 fourth-grade elementary school students and three experts (media, design, and content) who were involved in the product validation process. Data were collected through validation questionnaires, interviews, pretest-posttest assessments, and a metacognitive ability questionnaire. Data analysis was conducted using both descriptive and statistical techniques to measure the effectiveness of the developed media. The results indicated a significant improvement in students' metacognitive abilities after using the interactive PBL-based learning video, aligning with the primary objective of this research. The conclusion affirms that the development of interactive learning media based on PBL is effective in improving students' metacognitive abilities in IPAS learning. The implications of this study encourage teachers to integrate interactive media into classroom instruction to enhance student engagement and learning outcomes, while also strengthening digital literacy and teacher competence in addressing the challenges of 21st-century education.